Orientation of the liquid crystalline nickel phthalocyanine films confined between electrodes - Basova, Tamara V.; Hassan, Aseel; Durmuş, Mahmut; Gürek, Ayşe Gül; Ahsen, Vefa (Elsevier Science Sa, 2011)
In this paper, the orientation of thin films of tetra-substituted nickel phthalocyanine NiPcR4 (R = -SCH[CH2(OCH2CH2)(2)OC2H5](2)) deposited between two electrodes is studied by the method of polarized Raman spectroscopy and polarized microscopy. It has been shown that the films of NiPcR4 confined between ITO and metal (Al, Au) electrodes are characterized by homeotropic alignment while no homeotropic alignment was observed on ITO substrate with air interface. These findings are very important for the interpretation of electrical conduction through thin films of NiPcR4 in sandwich structures. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Thin film; Liquid crystal; Alignment